Comparing swallowing of capsule to endoscopic placement of capsule endoscopy in children - Burgess, Christopher J (JGH Open, 2017)
BACKGROUND AND AIM: Capsule endoscopy (CE) offers a method of directly visualizing areas of the small bowel not accessible by conventional endoscopy. Some children are unable to swallow the capsule requiring endoscopic placement under general anesthesia. The aim of the present study was to identify any differences between children requiring endoscopic placement and those able to swallow the capsule. METHODS: Retrospective chart review of consecutive CE in a tertiary pediatric center was conducted. Patient demographics, outcomes, and complications between the two groups were noted. Paired t‐test comparing continuous variables and Fisher exact test for categorical data were used. RESULTS: A total of 104 CEs were performed in 88 patients, median age 12.8 (range: 1.6–18.5) years. Almost half, 49% (51/104), swallowed the capsule. Children requiring endoscopic placement were significantly younger (9.8 vs 14.2 years; P < 0.001), lighter (34.5 vs 54.9 kg; P < 0.0001), and had longer small intestinal transit time (308 vs 229 min; P < 0.0001). Positive findings were more likely in those who swallowed the capsule (50% vs 30%, P = 0.017), likely a reflection of the indications for procedure. Poor views were found in 30% (16/53) of patients in the endoscopic placement group due to iatrogenic bleeding from biopsies taken from concurrent procedures but did not affect outcome or subsequent patient management. CONCLUSIONS: CE is safe and well tolerated in children. Children requiring endoscopic placement were significantly younger, lighter, had longer small intestine transit time, and less likely to have positive findings. Concurrent biopsies during capsule placement increase the likelihood of inadequate views but did not affect outcome or management.